2013
DOI: 10.1016/j.neulet.2013.08.042
|View full text |Cite
|
Sign up to set email alerts
|

The effect of parvalbumin deficiency on the acoustic startle response and prepulse inhibition in mice

Abstract: h i g h l i g h t s• PV−/− mice had smaller ASR amplitudes in response to relatively weak startling stimuli (80-90 dB SPL) in comparison with PV+/+ mice.• PPI of the ASR in PV−/− mice was less effective than in PV+/+ mice.• Mean ABR audiograms were found to be similar in both genotypes.The strength of the acoustic startle response (ASR) to short bursts of broadband noise or tone pips (4, 8 and 16 kHz) and the prepulse inhibition (PPI) of the ASR elicited by prepulse tones (4, 8 and 16 kHz) were measured in par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…A recently published study confirmed alterations of sensorimotor gating (PPI) in both sexes in all 3 mouse mutant lines 12 . In addition, altered numbers of parvalbumin-positive interneurons were observed in the thalamic reticular nucleus (TRN) of these mice, which is consistent with results showing that a deficiency of parvalbumin, a calcium binding protein, is known to affect PPI 13 .…”
Section: Introductionsupporting
confidence: 89%
“…A recently published study confirmed alterations of sensorimotor gating (PPI) in both sexes in all 3 mouse mutant lines 12 . In addition, altered numbers of parvalbumin-positive interneurons were observed in the thalamic reticular nucleus (TRN) of these mice, which is consistent with results showing that a deficiency of parvalbumin, a calcium binding protein, is known to affect PPI 13 .…”
Section: Introductionsupporting
confidence: 89%
“…Particularly, the differentiation of PV basket cells, a subpopulation of GABAergic neurons that regulate a critical period of plasticity in the cortex which depends on BDNF (for a review, see [54]), may play a role during the alteration of inhibitory strength in BDNF Pax2 -KOs. Likewise, elevated auditory startle amplitude and latencies in PV −/− mice suggested a specific role of PV basket cells for inhibitory circuits in auditory processing [55]. To investigate a role of PV for the observed changes in inhibitory strength in BDNF Pax2 -KO mice, we used antibodies for PV [56, 57] and antibodies for the 67-kDa isoform of GABAergic interneurons.…”
Section: Resultsmentioning
confidence: 99%
“…Only when KCC3 was targeted in parvalbumin-positive neurons did we detect a locomotor deficit similar to the one observed in the global knockout animals. Parvalbumin is a member of the large family of EF-hand calcium-binding proteins, which comprises more than 200 members in human [22]. It is essential for Ca 2+ homeostasis and the modulation of intracellular Ca 2+ concentration in specific populations of neurons [8].…”
Section: Discussionmentioning
confidence: 99%